Fundamentals of Entrepreneurship (ENT300) : Inspire Cottage Bridal / Mu’adh Abdullah Amir … [et al.] - Amir, Mu’adh Abdullah; Zulkifli, Zawanah Fatanah; Mohammad, Jaafar; George@Rosli, Julailah; Rahim, Muhammad Khidir; Norman, Muhamamd Faheem (2010)
Based on our research on the population and market size of bridal houses within Kuching, we discover a great business opportunity that we have decided to open up a Inspire Cottage Bridal. We will be offering services like wedding planning, bridal photography, dress rental and other services involves in our wedding packages. Inspire Cottage will an inspiration to the that visits our shop in building a precious valuable moment that they will treasure it all their life. In order to realize Inspire Cottage Bridal, every aspect of business establishment was seriously considered including the four most important element in business plan, administration, operation, marketing and financial plan.